PENGEMBANGAN KAWASAN PEDESAAN BERBASIS AGRIBISNIS DI KECAMATAN KELIMUTU, KABUPATEN ENDE, PROPINSI NUSA TENGGARA TIMUR - Leha, Ernesta (AGRICA, 2010)
The sector of agriculture experienced significant growth at the national level during 2008. This lead to the betterment of rural society or urban society. So does the Province of Nusa Tenggara Timur. The development of the sector of agriculture is significant enough but it is not quite optimal. It could be seen from the decreasing capability of absorbing manpower. This is the strong reason why rural areas need developing as agribusiness based-areas because the majority of the people who live in a rural area are a farmer. Knowing the prospect of an area if developed as an agribusiness based-areas needs specific research which can formulate priority of right strategies to develop agribusiness-based rural areas. This research was performed in the sub-district of Kelimutu, the regency of Ende, Province of Nusa Tenggara Timur. The internal factors which constitute the strength and the weakness are the availability of resources and land, farmer group, agricultural extension doer, cooperation, government official, human resources, socio-culture, technology, management, constitute the chance and barrier are tourism, stakeholder cooperation, foreign people, marketing, strategic location, the emergence of the new agricultural centre area, transportation problems, partnership, public demand, social problems, opposition, and rivalry. This research was used was qualitative ones which are obtained by in-depth interview, observation, questionnaire and document analysis. Meanwhile, the method and analysis technique which was used were (1) Matrix analysis of EFAS and EFAS; (2) SWOT analysis and (3) analysis of QSPM. From the research, formulations of alternative strategy aggressive which could be applied in the village of Kelimutu are (a) To increase the quality of human resource of Kelimutu in working out agribusiness-based natural resources and land, (b) To elevate the cooperation of stakeholder in developing the sub-district of Kelimutu because this area is a tourism area having a great potency of agribusiness and (c) To increase the capability of farmer management in the effort of agriculture, the processing and marketing of the agricultural stuff. Meanwhile, strategic priorities of intensive growth which could be applied are (a) Market penetration strategy to increase the market share of the agricultural product of the area through an extensive marketing effort, (b) Market Development Strategy which is intended to introduce agricultural product (from sub-district of Kelimutu) to new areas and in a global perspective, as well as the development of the international-scale market and (c) Product development strategy which is intended to increase sale by improving or modifying the existing product.